INVESTMENT DECISION OF BIOMEDICAL IMPLANT PRODUCTION UNDER UNCERTAINTY CONDITION: A MONTECARLO SIMULATION APPROACH - Setiawan, Suganta Handaru; Sumirat, Erman; Rahadi, Raden Aswin (Dynamic Management Journal, 2024)
PT. Langit Biru make investment project plan in biomedical implant production to grab the attractive market potential of biomedical implant and to diversify the business footprint in medical segment. Investment decision is made by considering the impacts of discrete risks using scenario analysis, and montecarlo simulations analysis for exploring the consequences of continuous risk to the project NPV.Based on the analysis, the project is feasible and exhibits a relatively low risk  under discrete and continuous risk where based on scenario analysis  NPV in worst case scenario is positive with value USD 433.621 (93% lower than the base case ) and montecarlo simulation expose that the project has 100% probability of positive NPV from 1000 simulation with NPV mean USD 6.224.042 that very close to the base NPV  USD 6.252.653 (-0,46% lower).